Experimental and simulation study of wind turbine grid connected - Nurul Izzati, Yusop (2012)
At present, it is very common to find renewable energy resources, especially wind power that connected to grid systems. In the growing electricity supply industry and open access market for electricity worldwide, renewable sources are getting added into the grid system. To assess the impact the wind turbine grid connected system, the knowledge of electrical characteristic of wind turbine and associated control equipments are required. This project presents experimental based and simulation for wind turbine by using MATLAB / SIMULINK. The presented control scheme provides the wind power flow to the grid through a converter and inverter. The advantages of using wind generator is environmental friendly refers than portable generator. As practically, wind generator does not use any raw material but portable generator uses the fuel or petrol to generate the electricity. Wind turbine grid connected system will be developed and established for the study. The elements of this project show how the voltage, current and power is being measured in this network environment. Experimental and simulation study on this entire control scheme is carried out by using MATLAB. The experimental and simulation results show the control performance and dynamic behaviour of the wind system it is to assess the impact on the grid system and load was used to simulate the real network environment. Results from experimental and research will be compared.